2019
DOI: 10.1002/cssc.201900560
|View full text |Cite
|
Sign up to set email alerts
|

Promotive Effect of Bicarbonate Ion on Two‐Electron Water Oxidation to Form H2O2 Catalyzed by Aluminum Porphyrins

Abstract: Two‐electron water oxidation initiated by one‐electron oxidation of aluminum porphyrins (AlTMPyP) is an alternative water oxidation to the conventional four‐electron pathway and could help to avoid the bottleneck subject of photon‐flux density in artificial photosynthesis. Here, a dramatic enhancement of the reactivity by bicarbonate ion in the two‐electron water oxidation to form H2O2 is reported. An addition of sodium carbonate (Na2CO3) controlled both catalytic current and product selectivity of the two‐ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 46 publications
2
29
0
Order By: Relevance
“…It is suggested that this process involves the oxidation of the Co III species formed in the first process to Co IV species, the observed peak potential fits DFT calculations for the redox potential of the Co IV/III (CO 3 ) 3 2−/3− couple (see below), which oxidize bicarbonate through reactions analogous to the reactions in Equations (11)–(13) that consist of the catalytic process observed. Very recently, a similar catalytic process has been reported for an Al porphyrin complex at 1.1 V (vs. Ag/AgCl) . The dependence of the second process on the pH is presented in Figure S12 (in the Supporting Information).…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…It is suggested that this process involves the oxidation of the Co III species formed in the first process to Co IV species, the observed peak potential fits DFT calculations for the redox potential of the Co IV/III (CO 3 ) 3 2−/3− couple (see below), which oxidize bicarbonate through reactions analogous to the reactions in Equations (11)–(13) that consist of the catalytic process observed. Very recently, a similar catalytic process has been reported for an Al porphyrin complex at 1.1 V (vs. Ag/AgCl) . The dependence of the second process on the pH is presented in Figure S12 (in the Supporting Information).…”
Section: Resultssupporting
confidence: 74%
“…Very recently,asimilarc atalytic process has been reported for an Al porphyrin complex at 1.1 V( vs. Ag/AgCl). [71] The dependence of the second process on the pH is presented in Figure S12 (in the Supporting Information). Twoe ffects are observed: a) the peak potentialshifts considerably to lower potentials with the increase in the pH;b )the current increases considerably with the increasei nt he pH.…”
Section: The Second Wave Co Iv/iiimentioning
confidence: 99%
See 2 more Smart Citations
“…Inspired by this phenomenon and previous studies in electrogenerated chemiluminescence 29 , 30 and peroxycarbonate synthesis 31 , here we hypothesize that CO 2 (or carbonate as its ionic form in water) may serve as an effective mediator to promote the H 2 O 2 pathway in electrochemical water oxidation (Fig. 1a ) 32 34 . Using fluorine doped tin oxide (FTO) as a model catalyst electrode, we demonstrated high H 2 O 2 selectivity up to 87%, delivered high H 2 O 2 partial current densities up to 1.3 A cm −2 , and achieved a long-term stable and continuous H 2 O 2 generation for 250 hours with over 80% H 2 O 2 selectivity at 150 mA cm −2 current density in carbonate solutions.…”
Section: Introductionsupporting
confidence: 53%